Purification And Characterization Of Protease From Artocarpus Integer Leaf - Zulfigar, Siti Balqis (2012)
The presence of a protease in Artocarpus integer leaves, which can be used as a meat tenderiser, was verified by the presence of a band at 69 kDa, using caseinolytic zymography and sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS PAGE). Purification by temperature-phase partitioning with 6 % (v/v) Triton X-114, 44 % (w/v) ammonium sulphate precipitation and gel filtration chromatography yielded a preparation with a 12-fold increase in enzyme purity and a final specific activity of 76.67 U/mg. The purified protease was maximally active at 40ºC and at pH 10.0.